Indian Scenario on Custodial Torture with Special Reference to Woman Victims: Examining the Impact of Custodial Torture on Women and Vulnerable Groups in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In India, torture is widely practiced in executive function especially in administration of criminal justice system by the police. The main cause of such continuity is the failure or unwillingness of governments to hold an inquiry and punish those who are found guilty. The redress for the victims of torture is not possible as they are not aware of their right nor the resources required seeking it. Custodial crimes are increasing rapidly and in Most of the cases the victims of torture are generally Dalits and Adivasi’s Women, Children, Politicians and Human Rights Activists and Weaker Sections of the Community